2013
DOI: 10.1186/1477-9560-11-10
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban and other novel oral anticoagulants: pharmacokinetics in healthy subjects, specific patient populations and relevance of coagulation monitoring

Abstract: Unlike traditional anticoagulants, the more recently developed agents rivaroxaban, dabigatran and apixaban target specific factors in the coagulation cascade to attenuate thrombosis. Rivaroxaban and apixaban directly inhibit Factor Xa, whereas dabigatran directly inhibits thrombin. All three drugs exhibit predictable pharmacokinetic and pharmacodynamic characteristics that allow for fixed oral doses in a variety of settings. The population pharmacokinetics of rivaroxaban, and also dabigatran, have been evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 80 publications
9
115
0
1
Order By: Relevance
“…18,19 A 150-mg oral dose of dabigatran has a maximum plasma concentration of 110 ng/mL. 20,21 Rivaroxaban stock was prepared by agitation of a 20-mg rivaroxaban tablet in a 1:1 dimethyl sulfoxide and water solution, which was diluted to a final concentration of 20 ng/lL of rivaroxaban in 1:1 dimethyl sulfoxide and water. Tubes of citrated blood were spiked with this rivaroxaban stock to create final concentrations of 500, 89, and 22 ng/mL in citrated whole blood.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 A 150-mg oral dose of dabigatran has a maximum plasma concentration of 110 ng/mL. 20,21 Rivaroxaban stock was prepared by agitation of a 20-mg rivaroxaban tablet in a 1:1 dimethyl sulfoxide and water solution, which was diluted to a final concentration of 20 ng/lL of rivaroxaban in 1:1 dimethyl sulfoxide and water. Tubes of citrated blood were spiked with this rivaroxaban stock to create final concentrations of 500, 89, and 22 ng/mL in citrated whole blood.…”
Section: Sample Preparationmentioning
confidence: 99%
“…12,22 An oral dose of 10 mg of rivaroxaban has a maximum plasma concentration of 141 ng/mL. 21,23 Apixaban stock was prepared in a similar manner from a 2.5-mg apixaban tablet, with final concentrations of 1000, 500, and 250 ng/mL in whole blood. Apixaban is approved for the prevention of venous thromboembolism in elective hip or knee replacement surgery (2.5 mg twice daily) and for the prevention of stroke and systemic embolism in patients with nonvalvular atrial fibrillation (5 mg twice daily).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Their lack of reversibility is largely documented in the literature, however this is not uncommon for other anticoagulant agents such as low-molecular-weight-heparins (LMWHs) and pentasaccharides [42]. Dosages for the NOACs are provided in Table 1 below [39,43,44]. …”
Section: Clinical Indications and Dosingmentioning
confidence: 99%
“…On oral administration, prasugrel has a rapid and nearly complete (>80%) gastrointestinal absorption, with peak maximal platelet inhibition occurring within 1 hour and a half-life of 7 hours [47,48]. Preclinical and clinical studies have revealed that prasugrel has been demonstrated to have a faster onset of action, increased potency and less response variability with respect to platelet inhibitory activity as compared with clopidogrel [44] Ticagrelor (Brillinta®) Ticagrelor is an orally administered nonthienopyridine, which directly and reversibly inhibits the P2Y 12 receptor. It is an ATP analogue that binds reversibly in a non-competitive manner to the P2Y 12 receptor at distinct sites to ADP and the thienopyridines.…”
Section: Prasugrel (Effient®)mentioning
confidence: 99%
“…It has been approved by EMEA and FDA for the prevention of venous thromboembolism in adult patients after total hip replacement or total knee replacement surgery [3][4][5][6] . Rivaroxaban is available in the market under the brand name Xarelto ® as 10mg tablets in Europe and US.…”
Section: Introductionmentioning
confidence: 99%